2015
DOI: 10.1097/ico.0000000000000309
|View full text |Cite
|
Sign up to set email alerts
|

Topical NSAIDs Effect on Corneal Sensitivity

Abstract: All 4 currently available NSAIDs demonstrated anesthetic effects similar to brand diclofenac and brand ketorolac.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 8 publications
0
16
1
1
Order By: Relevance
“…The data presented in this study indicates that neither topical diclofenac nor flurbiprofen has an effect on corneal sensitivity in normal, nonbrachycephalic dogs after multiple‐drop dosing or chronic, twice‐daily dosing for 30 days. This is in direct contrast to humans in which topical diclofenac has been shown to decrease corneal sensitivity after single and multiple doses . Of importance to the present study, evaluation in humans has shown that diclofenac consistently decreases corneal sensitivity while flurbiprofen does not have the same effect .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data presented in this study indicates that neither topical diclofenac nor flurbiprofen has an effect on corneal sensitivity in normal, nonbrachycephalic dogs after multiple‐drop dosing or chronic, twice‐daily dosing for 30 days. This is in direct contrast to humans in which topical diclofenac has been shown to decrease corneal sensitivity after single and multiple doses . Of importance to the present study, evaluation in humans has shown that diclofenac consistently decreases corneal sensitivity while flurbiprofen does not have the same effect .…”
Section: Discussionmentioning
confidence: 99%
“…In humans, topical NSAIDs have been shown to decrease corneal sensitivity . Additionally, topical NSAIDs have been shown to attenuate corneal nerve responses in cats .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 10 healthy volunteers, bromfenac 0.07 % (administered as one drop every 5 min for a total of four drops) significantly (p \ 0.001) reduced corneal sensitivity versus baseline [11]. Limited data (from an abstract) from 24 patients (38 eyes) participating in a pilot study following cataract surgery showed that therapy with bromfenac 0.07 % once daily plus loteprednol etabonate 0.05 % taper plus besifloxacin 0.6 % three-times daily minimized macular thickening [12].…”
Section: Introductionmentioning
confidence: 96%
“…In addition, the sensations experienced at the ocular surface are difficult to quantify in each subject because sensation perception can be affected by several factors including medications, systemic conditions, and the environment. 17,19,[42][43][44][45] Even the various receptors discussed previously (mechanoreceptors, polymodal receptors, and cold receptors) have been shown to affect each other. 46,47 These factors may need to be considered together to fully understand the association between the tear-producing glands and the ocular surface sensations.…”
Section: Discussionmentioning
confidence: 96%